Analysis of land structure in the Uruçuí-Preto river basin, Piauí (Research, Society and Development, 2023)
The process of expanding the agricultural frontier in the Brazilian Cerrado has been intensified by the attractive price of land, infrastructure, and state incentives created to promote agribusiness, in addition to favorable natural conditions. In this sense, the recent productive and extractive dynamics of the soil and natural resources put water, a fundamental element for human life, at risk. In this study, the land infrastructure of the municipalities comprising the Uruçuí-Preto River Watershed was analyzed, using the public cadastre bases of the Land Management System (SIGEF) and the National Rural Property Certification System (SNCI). These municipalities have high production of agricultural commodities aimed at export, particularly soybeans. As a result, it was found that the municipality of Uruçuí, recognized in the literature as a pioneer in attracting agribusiness companies, has 30.79% of the total number of properties defined as small and medium-sized properties, while municipalities such as Santa Filomena and Baixa Grande do Ribeiro present 85.47% and 82.92%, respectively. The results also highlight the productive agricultural potential of these municipalities, while evidencing the concentration of land ownership in this region.